2015 IEEE International Conference on Industrial Technology (ICIT) 2015
DOI: 10.1109/icit.2015.7125473
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-order model of a half-bridge series resonant inverter for power control in domestic induction heating applications

Abstract: Abstract--From the controller design framework, a simple analytical model that captures the dominant behavior in the range of interest is the optimal. When modeling resonant circuits, complex mathematical models are obtained. These high-order models are not the most suitable for controller design. Although some assumptions can be made for simplifying these models, variable frequency operation or load uncertainty can make these premises no longer valid. In this work, a systematic modeling order reduction techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…PCA has also been used in [16] to approximate the frequency response of a fourth‐order DC–DC converter by a second‐order system. Balanced truncation (BT) has been used in [17] to derive ROM for a half‐bridge series resonant inverter. Order reduction techniques have been applied to high‐fidelity magnetic equivalent circuits incorporating saturation, relative motion and multiple winding systems yielding efficient simulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…PCA has also been used in [16] to approximate the frequency response of a fourth‐order DC–DC converter by a second‐order system. Balanced truncation (BT) has been used in [17] to derive ROM for a half‐bridge series resonant inverter. Order reduction techniques have been applied to high‐fidelity magnetic equivalent circuits incorporating saturation, relative motion and multiple winding systems yielding efficient simulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency response of the fourth-order converter is approximated by a second-order system. The work in [18] focusses on deriving a reduced-order model of half-bridge series resonant inverters (HBSRI) for use in induction heating applications using balanced truncation. In [19], order reduction techniques are applied on high-fidelity magnetic equivalent circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The SVAP approach or similar techniques have been applied to mixed systems or converters operating in DCM where one variable can be considered static. Although after applying SVAP/residualization a valid low frequency HBSRI model is obtained [27], it is not formally valid to separate the dynamics of v c and i L because a HBSRI is not a mixed system. In order to improve the dynamic results, a SVADP technique is proposed in this paper.…”
Section: ( )mentioning
confidence: 99%
“…In this paper, it's shown that residualization of series resonant capacitor voltage is identical to Slowly Varying Amplitude and Phase (SVAP) approach [22]. In order to provide better dynamic results than residualization in [27], a Slowly Varying Amplitude Derivative and Phase (SVADP) technique is proposed. The obtained results match with the ones recently published in [11] for a SRC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation